Farm level impact study of power tiller operated seeder on service providers livelihood in some selected sites of Bangladesh (Bangladesh Journal of Agricultural Research, 2016)
The custom hiring of power tiller operated seeder (PTOS) is highly profitable at farm level and service providers could improve their livelihood through this machine. The data and information on these aspects are scarce in Bangladesh. Therefore, an attempt was made to conduct this study to assess the uses pattern and the impacts of PTOS operations on service providers livelihood. A total of 53 service providers were randomly selected and interviewed for this study from Dinajpur and Rajbari districts. The study revealed that most respondents provided PTOS services almost throughout the year. The custom hiring of PTOS created many positive impacts on the livelihoods of the service providers. PTOS made a remarkable improvement in the livelihoods of its service providers in the study areas. The respondent service providers experienced a considerable increase in their land holdings (8.6%), annual income (63.4%), livestock resources (44%), farm equipment (20%), household assets position, and dwelling houses (42%). The increased income of beneficiaries are mostly spent on farm machinery, nutritious food, cloths, health care, education, and making of houses that indicate higher standard of riding to some extent, compared to pre PTOS service period. The service providers faced some problems like higher fuel cost, lack of riving facility, non-availability and higher price of spare parts, roller jam, and lack of trained driver. Financial support and technical assistance regarding PTOS should be made available by the government for service providers and local manufacturers for the higher adoption of PTOS in Bangladesh.Bangladesh J. Agril. Res. 40(4): 669-682, December 2015